Ceftriaxone and cefazolin attenuate the cue-primed reinstatement of alcohol-seeking - Weiland, Ana; Garcia, Steven; Knackstedt, Lori A. (Frontiers in Pharmacology, 2015)
Alcohol consumption and the reinstatement of alcohol-seeking rely on glutamate and GABA transmission. Modulating these neurotransmitters may be a viable treatment strategy to prevent alcohol relapse. N-acetylcysteine (NAC) and the antibiotic ceftriaxone (CEF) alter the glial reuptake and release of glutamate while the antibiotic cefazolin (CEFAZ) modulates GABA signaling without affecting glutamate. Here we used the extinction-reinstatement model of relapse to test the ability of these compounds to attenuate the reinstatement of alcohol-seeking. Male Sprague-Dawley rats were trained to self-administer 20% (v/v) alcohol in the home cage using an intermittent schedule (24 hr on, 24 hr off) for 12 sessions. Subsequently, animals self-administered alcohol during daily 45-min operant sessions for 26 sessions, followed by extinction training. We tested whether chronic administration of NAC, CEF or CEFAZ attenuated the cue-primed reinstatement of alcohol-seeking. CEF and CEFAZ attenuated cue-primed reinstatement of alcohol-seeking while NAC had no effect. We subsequently investigated whether CEF and CEFAZ alter the self-administration of sucrose and chow pellets and if CEFAZ attenuates the reinstatement of cocaine-seeking. The operant self-administration of regular chow and sucrose was not altered by either CEF or CEFAZ. CEFAZ had no effect on cocaine reinstatement, a behavior that has been strongly tied to altered glutamate homeostasis in the nucleus accumbens. Thus the ability of CEFAZ to attenuate alcohol reinstatement likely does not involve the glial modulation of glutamate levels. The dampening of GABA transmission may be a common mechanism of action of cefazolin and ceftriaxone.